Bridging the barriers to effective life cycle management uptake : a framework for primary industry sectors : a thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy in Science, Life Cycle Management, Massey University, New Zealand - Seidel-Sterzik, Helene (Massey University, 2019)
There is a rising global awareness of environmental problems and wider sustainability issues in business and society. Examples of environmental issues that are particularly topical include carbon emissions and climate change, waste and pollution, water consumption and impacts on biodiversity. One approach to incorporate environmental sustainability in organisations is the implementation of Life Cycle Management (LCM). LCM is a comprehensive and integrated approach towards measuring and managing environmental impacts. LCM involves sharing responsibility for addressing environmental impacts across the entire supply chain of products and services, extending from raw material extraction to end-of-life. In New Zealand, the environmental performance of products is particularly important as export markets are geographically distant and additional environmental impacts occur due to extensive transport to deliver products to end users. Additionally, New Zealand has an image of being “green and clean” which needs to be justified, particularly in discerning export markets such as Europe and Japan. Governments in those export markets often have stringent legislation in place to encourage the uptake of environmental improvement projects and ecologically responsible behaviour. Likewise, customers increasingly use environmental factors to guide their purchasing decisions. Therefore, it is important for New Zealand organisations to comply with legislation and align with customer expectations about the environmental performance of their products and services. The New Zealand economy relies heavily on primary exports with around 70% of the country’s export revenue being generated by primary industries (Ministry for Primary Industries, 2016; Trade, 2019). Successful sector-wide uptake of LCM has the potential to facilitate effective measurement and management of the environmental impacts caused by the New Zealand primary industries. Thus, New Zealand can strengthen its competitiveness in the global marketplace by maintaining and reinforcing the country’s “green and clean” image and being able to respond to threats such as the “food miles” concept. A large number of organisations in primary industry supply chains are Small and Medium Sized Enterprises (SMEs). Compared to large companies, SMEs face particular challenges when it comes to uptake of environmental initiatives. These include limited resources, lack of knowledge around market requirements, and lack of expertise in the environmental area. The aim of this PhD research was therefore to develop an approach that supports primary industry sectors to effectively evaluate, monitor and demonstrate their LCM practices based on globally relevant criteria. In particular, this research examined and tested the use of a sector-based, as opposed to individual organisation-based, approach to the implementation of LCM as an effective means of driving change amongst primary industry SMEs and overcoming the barriers they face during LCM uptake. Thus far, the focus of research into the enablers and barriers to uptake of LCM in SMEs has been on individual companies. However, a sector-based approach may allow more effective measurement and management of environmental impacts associated with supply chains. The research design involved four elements and triangulated a mix of methods, including literature-based research, face-to-face interviews, and an online survey. The New Zealand kiwifruit and aquaculture industry sectors were used as case studies to inform development of a framework for evaluating, monitoring and demonstrating LCM in primary industry sectors that are comprised largely of SMEs. The thesis has been written using a paper style with four main chapters that cover each of the four elements. Chapter 3 documents the theoretical foundation by synthesizing the literature related to enablers and barriers to uptake of LCM in organisations, related literature on supply chain management (SCM), and on the characteristics of SMEs that influence their ability to engage in change management. This led to the identification of eight factors that affect successful LCM uptake within industry sectors. On this basis it was identified that a sector-based approach could facilitate the implementation of LCM in primary industry sectors and support the large number of SMEs in those industry sectors efficiently. The academic contribution of this research phase includes the synthesis of barriers and enablers to successful sector-wide LCM uptake, as well as identification of a sector-based approach for effective implementation of LCM in supply chains. Chapter 4 summarises a study of LCM in the New Zealand kiwifruit sector. An online survey was undertaken of kiwifruit growers from various regions in New Zealand. The academic contributions of this element include the identification of the specific barriers and enablers to successful LCM uptake in the New Zealand kiwifruit sector. During this research, it was identified that knowledge management using technology is a key research area that should be considered to ensure that knowledge and information relating to LCM are effectively transferred between supply chain partners in order to facilitate the successful implementation of a sector wide sustainability strategy. Chapter 5 describes the development of a prototype LCM Uptake Evaluation Framework (LUEF) based on the literature review (Chapter 1) and the kiwifruit case study (Chapter 4). The LUEF is a capability maturity model designed to enable both individual companies and industry sectors to assess themselves against the factors that affect the uptake of LCM. The LUEF provides a methodological contribution to academic knowledge in the area of LCM and a practical tool to support companies and industry sectors to evaluate their maturity with respect to LCM. Chapter 6 describes the development of an Information Technology (IT) platform to support the effective management of an LCM programme using a sector-based approach. The IT platform aims to address the shortcomings of the LUEF developed in the previous chapter. In order to use it at a larger scale and support individual organisations as well as industry sectors in their decision-making processes to improve their environmental performance on an ongoing basis, an online platform is suggested. The platform was designed to allow individual organisations to input their data at the time of their convenience, and for industry stakeholders to access the aggregated and industry-average data. The New Zealand aquaculture industry was used as a case study to inform development of the IT platform, and industry stakeholders particularly highlighted the ease of communication and collaboration, which was identified as a key enabler of successful LCM uptake on a sector-wide basis. Key contributions during this research phase involved the development and refinement of an online software platform to facilitate the implementation of a sector-based LCM strategy, including setting industry targets, developing best practice guidelines, and identifying improvement projects. Future research should focus on wider dissemination of the LUEF, facilitated by IT platforms, across other primary industry sectors with different structures compared to the kiwifruit and aquaculture sectors in New Zealand.
Keywords: Agricultural industries; New Zealand; Management; Product life cycle; Environmental aspects; Sustainability; Small business; 300208 Farm management, rural management and agribusiness